Preparation of colored recycled polyethylene terephthalate nanofibers from waste bottles: Physicochemical studies - Mehdi, Mujahid; Mahar, Faraz Khan; Qureshi, Umair Ahmed; Khatri, Muzamil; Khatri, Zeeshan; Ahmed, Farooq; Kim, Ick Soo (Advances in Polymer Technology, 2018)
In this study, polyethylene terephthalate‐based waste drinking bottles have been used to develop colorful nanofibers via electrospinning. The recycled polyethylene terephthalate (r‐PET) nanofibers were characterized through scanning electron microscopy (SEM), Fourier transform infra red spectroscopy (FTIR), X‐ray diffraction (XRD), and X‐ray photo electron spectroscopy (XPS) techniques and were explored for advanced colorful applications. To prepare colorful r‐PET nanofibers, two different disperse dyes, C.I Disperse Blue 56 (DB‐56) and C.I Disperse Red 167:1 (DR 167:1), were used by dope dyeing technique. The dope dyeing of r‐PET nanofibers was optimized by determining the effects of different polymer concentrations (9%–15%) and dye concentrations (1%–7%). The proposed r‐PET nanofibers offer many advantages such as good color fastness, good mechanical strength, save processing energy, and time compared to other conventional nanofibers.